2014
DOI: 10.4081/ijas.2014.3242
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Plasma Antioxidant Activity in Weaned Piglets by Plant Polyphenols

Abstract: This study was conducted to evaluate the effect of plant polyphenols (PP) on antioxidant activity in weaned piglets. First, a uniform design, one optimising an experimental technique that can rationally arrange the concentrations of mixture components, was used to obtain the best PP mixture of apple, grape seed, green tea and olive leaf polyphenols based on in vitro antioxidant capacity and inhibitory action on bacterial growth. Second, the optimised PP mixture was tested in vivo with an efficacy trial on pigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
(33 reference statements)
4
27
0
Order By: Relevance
“…Similar results were reported by other authors who observed an improvement in the antioxidant status, an increase in the activity of antioxidant enzymes and a decrease in plasma MDA levels in weaned piglets fed diets supplemented with polyphenols. Dietary polyphenol supplementation improved the health status and growth performance of piglets (Zhang et al 2014;Hao et al 2015;Chen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by other authors who observed an improvement in the antioxidant status, an increase in the activity of antioxidant enzymes and a decrease in plasma MDA levels in weaned piglets fed diets supplemented with polyphenols. Dietary polyphenol supplementation improved the health status and growth performance of piglets (Zhang et al 2014;Hao et al 2015;Chen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Zhang et al. (), supplementation of a basal diet with a mixture of polyphenols extracted from apple, grapes, green tea and olive leaves (at a level of 1 g/kg diet) reduced concentration of MDA in plasma of weaned piglets but had no effect on the total antioxidative capacity and activities of several antioxidant enzymes in plasma. The overall conclusion of the few studies performed so far is that supplementation of polyphenols improves the antioxidative status and ameliorates oxidative stress in pigs subjected to prooxidative treatment.…”
Section: Effects Of Polyphenols On Oxidative Stress and Inflammationmentioning
confidence: 98%
“…Proanthocyanidins extracted from other plants have also aroused interest because of their uses in animal nutrition. Park et al (2011), for example, reported that a proanthocyanidin-rich extract from Pinus radiata bark modulates immunity in chickens, whereas Zhang et al (2014) have shown that a prepared plant polyphenol mixture increases the antioxidant ability of plasma in piglets.…”
Section: Introductionmentioning
confidence: 99%